Absence of associations between influenza vaccines and increased risks of seizures, Guillain–Barré syndrome, encephalitis, or anaphylaxis in the 2012–2013 season. (4th February 2014) - Kawai, Alison Tse; Li, Lingling; Kulldorff, Martin; Vellozzi, Claudia; Weintraub, Eric; Baxter, Roger; Belongia, Edward A.; Daley, Matthew F.; Jacobsen, Steven J.; Naleway, Allison; Nordin, James D.; Lee, Grace M.
ABSTRACT Purpose We conducted weekly surveillance for pre‐specified adverse events following receipt of the 2012–2013 influenza vaccines in the Vaccine Safety Datalink (VSD). Methods For each outcome, risk intervals (i.e., period after vaccination with a potentially increased risk) were defined on the basis of biologic plausibility and prior literature. Seizures following inactivated influenza vaccine (IIV) were monitored in children in three age groups (6–23 months, 24–59 months, and 5–17 years) using a self‐controlled risk interval design. We also monitored for Guillain–Barré syndrome, encephalitis, and anaphylaxis following IIV in patients ≥6 months of age using a cohort design with historical controls. In the risk intervals following live attenuated influenza vaccine (LAIV), we collected weekly counts of Guillain–Barré syndrome, encephalitis, and anaphylaxis in patients ages 2–49. Among LAIV vaccinees, numbers of expected events based on rates in historical controls were calculated, adjusted for age and site. Results At the end of surveillance, approximately 3.6 million first doses of IIV and 250 000 first doses of LAIV had been administered in the VSD. No elevated risks were identified in risk intervals following 2012–2013 IIV, as compared with a self‐matched control interval or to historical controls. For each outcome, fewer than three events occurred in the risk interval following 2012–2013 LAIV, and we thus were unable to estimate measures of relative risks. Conclusions No increased risk was identified for any of the pre‐specified outcomes following 2012–2013 influenza vaccinations in the VSD. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.